Dimer pairing on the c-alloyed si(001) surface - Leifeld, Oliver; Grützmacher, Detlev A.; Kelires, Pantelis C. (My University, 1999)
The initial stages of carbon alloying into the Si(001) surface are studied by scanning tunneling microscopy (STM) and density functional theory. Carbon increases the surface roughness compared to the clean surface and induces a c(4 × 4) reconstruction. To explain experimental observations, we propose a novel surface reconstruction model that involves pairing of Si dimers mediated by the presence of a complex of a C dimer and four nearest neighbor subsurface C atoms. The model is backed by total energy and thermal stability simulations. Its calculated surface charge density agrees well with the filled state STM images.
Keywords: Carbon; Energy